The Mediation Role of Review Helpfulness, Customers Trust, and Brand Attitude Towards Positive e-WOM and Purchase Intention in Cosmetic Shopping Experience - Lulu Puspita Anggraini; Nurdin Sobari (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2023)
Objective: This study aims to examine the effectiveness of positive electronic word of mouth (e-WOM) in influencing the purchase intention of the cosmetic retailer and the role of review helpfulness, customers' trust in e-WOM, and the role of brand attitude as a mediator in the relationship. Design/Methods/Approach: This study adopts descriptive quantitative research methods. The populations are women who frequently buy cosmetic products and are selected using non-probability and purposive sampling techniques. The data collection used an online survey with 155 respondents. Afterward, Partial Least Square–Structural Equation Modeling (PLS-SEM) was used to test the hypotheses. Findings: Findings indicate that positive e-WOM has a positive and significant effect on review helpfulness. Review helpfulness also positively and significantly affects customers' trust in e-WOM and brand attitude. This study also found that customers' trust in e-WOM and brand attitude positively and significantly affected purchase intention. In addition, this study also found that review helpfulness has a positive and insignificant effect on purchase intention. Moreover, results suggest that review helpfulness, customers' trust in e-WOM, and brand attitude positively and significantly mediate the effect of positive e-WOM on purchase intention.  Originality: This study contributes to the marketing literature by using the positive e-WOM variable to see its effect on review helpfulness, customers' trust in e-WOM, brand attitude, and purchase intention in the cosmetic retailing context. Practical/Policy Implications: Given that positive e-WOM improves customers' purchase intention through review helpfulness, trust in e-WOM, and brand attitude, cosmetic retailers are recommended to encourage their customers to post a review on the retailers' websites or applications. In addition, Cosmetic retailers also recommend displaying the customers' reviews. Hence, the reviews may help other customers know about the products before buying.